Cardiorespiratory Fitness and Attentional Control in the Aging Brain - Prakash, Ruchika S.; Voss, Michelle W.; Erickson, Kirk I.; Lewis, Jason; Chaddock, Laura; Malkowski, Edward; Alves, Heloisa; Kim, Jennifer S.; Szabo, Amanda; White, Siobham; Wojcicki, Thomas; Kramer, Arthur F.; et al. (Frontiers in Human Neuroscience, 2011)
A growing body of literature provides evidence for the prophylactic influence of cardiorespiratory fitness on cognitive decline in older adults. This study examined the association between cardiorespiratory fitness and recruitment of the neural circuits involved in an attentional control task in a group of healthy older adults. Employing a version of the Stroop task, we examined whether higher levels of cardiorespiratory fitness were associated with an increase in activation in cortical regions responsible for imposing attentional control along with an up-regulation of activity in sensory brain regions that process task-relevant representations. Higher fitness levels were associated with better behavioral performance and an increase in the recruitment of prefrontal and parietal cortices in the most challenging condition, thus providing evidence that cardiorespiratory fitness is associated with an increase in the recruitment of the anterior processing regions. There was a top-down modulation of extrastriate visual areas that process both task-relevant and task-irrelevant attributes relative to the baseline. However, fitness was not associated with differential activation in the posterior processing regions, suggesting that fitness enhances attentional function by primarily influencing the neural circuitry of anterior cortical regions. This study provides novel evidence of a differential association of fitness with anterior and posterior brain regions, shedding further light onto the neural changes accompanying cardiorespiratory fitness.